Therapeutic or spontaneous Helicobacter pylori eradication can obscure magnifying narrow-band imaging of gastric tumors - Kobayashi, Masaaki; Hashimoto, Satoru; Mizuno, Ken-ichi; Takeuchi, Manabu; Sato, Yuichi; Watanabe, Gen; Ajioka, Yoichi; Azumi, Motoi; Akazawa, Kouhei; Terai, Shuji (Endoscopy International Open, 2016)
Background and study aims: We previously reported that narrow-band imaging with magnifying endoscopy (NBI-ME) revealed a unique “gastritis-like” appearance in approximately 40 % of early gastric cancers after Helicobacter pylori eradication. Because rates of gastric cancer are increasing in patients with non-persistent infection of H. pylori, we aimed to clarify contribution factors to obscure tumors after therapeutic or spontaneous eradication.Patients and methods: NBI-ME findings were examined retrospectively in 194 differentiated-type adenocarcinomas from H. pylori-negative patients with prior eradication therapy (83 patients) or without prior eradication therapy (72 patients). A gastritis-like appearance under NBI-ME was defined as an orderly microsurface structure and/or loss of clear demarcation with resemblance to the adjacent, non-cancerous mucosa. The correlation of this phenomenon with the degree of atrophic gastritis, determined both histologically in the adjacent mucosa and endoscopically, was evaluated.Results: The tumor-obscuring gastritis-like appearance was observed in 42 % and 23 % of the patients in the H. pylori eradication and non-eradication groups, respectively. The development of this appearance was affected by the histological grade of atrophy (P = 0.003) and intestinal metaplasia (P < 0.001) on univariate analysis. Multivariate analysis revealed an odds ratio of 0.25 (95 % confidence interval 0.10 – 0.61, P = 0.002) for an endoscopically severe extent of atrophy, independently of eradication therapy.Conclusions: An endoscopically mild or moderate extent of atrophy is associated with a gastritis-like appearance under NBI-ME in currently H. pylori-negative gastric cancers. Surveillance endoscopy should be performed carefully after successful eradication or spontaneous elimination of H. pylori, particularly in patients with non-severe atrophic background mucosa.